Takotsubo Cardiomyopathy in the Setting of Tension Pneumothorax - Michael Gale; Pablo Loarte; Brooks Mirrer; Thierry Mallet; Louis Salciccioli; Alison Petrie; Ronny Cohen (Case Reports in Critical Care)
Background. Takotsubo cardiomyopathy is defined as a transient left ventricular dysfunction, usually accompanied by electrocardiographic changes. The literature documents only two other cases of Takotsubo cardiomyopathy in the latter setting. Methods. A 78-year-old female presented to the ED with severe shortness of breath, hypertension, and tachycardia. On physical exam, heart sounds (S1 and S2) were regular and wheezing was noticed bilaterally. We found laboratory results with a WBC of 20.0 (103/μL), troponin of 16.52 ng/mL, CK-mb of 70.6%, and BNP of 177 pg/mL. The patient was intubated for acute hypoxemic respiratory failure. A chest X-ray revealed a large left-sided tension pneumothorax. Initial echocardiogram showed apical ballooning with a LVEF of 10–15%. A cardiac angiography revealed normal coronary arteries with no coronary disease. After supportive treatment, the patient’s condition improved with a subsequent echocardiogram showing a LVEF of 60%. Conclusion. The patient was found to have Takotsubo cardiomyopathy in the setting of a tension pneumothorax. The exact mechanisms of ventricular dysfunction have not been clarified. However, multivessel coronary spasm or catecholamine cardiotoxicity has been suggested to have a causative role. We suggest that, in our patient, left ventricular dysfunction was induced by the latter mechanism related to the stress associated with acute pneumothorax.